Study on the Dynamic Relationship between Investor Sentiment and Market Fluctuation from the Perspective of Behavioral Finance - Yan, Lu (Transactions on Social Science, Education and Humanities Research, 2023)
This paper studies the influence of investor sentiment on market volatility and management strategy, including the definition and classification of investor sentiment, analyze the characteristics and influencing factors, discusses the correlation of mood and market volatility, the emotional infectious effect and the influence of market volatility and apply investor sentiment index, summarize the advantages and limitations, and puts forward the investor sentiment management strategy, the influence of investor sentiment on market volatility, and provides a new idea for the management of investor sentiment.